2021
DOI: 10.1007/s10479-021-04352-1
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on kernelizing and computing unrooted agreement forests

Abstract: Phylogenetic trees are leaf-labelled trees used to model the evolution of species. Here we explore the practical impact of kernelization (i.e. data reduction) on the NP-hard problem of computing the TBR distance between two unrooted binary phylogenetic trees. This problem is better-known in the literature as the maximum agreement forest problem, where the goal is to partition the two trees into a minimum number of common, non-overlapping subtrees. We have implemented two well-known reduction rules, the subtree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The random trees were generated following the same protocol as used in in [16], which we summarize here. Starting with an empty rooted binary phylogenetic tree, we place a taxon from X on one side of the root with probability 1 2 , and on the other side with probability 1 2 , and then recurse on the two sides of the root until the leaves are reached.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The random trees were generated following the same protocol as used in in [16], which we summarize here. Starting with an empty rooted binary phylogenetic tree, we place a taxon from X on one side of the root with probability 1 2 , and on the other side with probability 1 2 , and then recurse on the two sides of the root until the leaves are reached.…”
Section: Applicationsmentioning
confidence: 99%
“…This was noted in [12] where an algorithm based on listing g 2 characters was used to design a simple but surprisingly practical algorithm for exact computation of maximum parsimony distance [6] phylogenetic trees. This later became the foundation for a far more scalable samplingbased heuristic for the same problem [16]; both the listing and sampling leverage the dynamic programming scaffolding originally used to actually count g k . In [12] it was also observed that the maximum agreement forest problem [2] can be solved in time O(2.619 n ) by listing g 1 characters.…”
Section: Applicationsmentioning
confidence: 99%
“…54(lg n+1) , as claimed in Theorem 13. To do this, we use an ILP formulation of the unrooted MAF problem by Van Wersch et al [13]. For a pair of trees (T 1 , T 2 ) on X , let Q be the set of incompatible quartets of T 1 and T 2 .…”
Section: Finding Leg-disjoint Incompatible Quartetsmentioning
confidence: 99%
“…Such a set of quartets does not give a parsimony distance that is at least the number of quartets, but the parsimony distance is still linear in the number of quartets. We present a primal-dual algorithm based on an ILP formulation of the maximum agreement forest problem [13] that finds such a set Q of incompatible quartets and an AF of size O(|Q| • lg |X |). This establishes the key claim that…”
Section: Introductionmentioning
confidence: 99%